Consecutive, Resting, Long-Duration Hyperoxic Exposures Alter Neuromuscular Responses During Maximal Strength Exercises in Trained Men - Myers, Christopher M.; Kim, Jeong-Su; Florian, John P. (Frontiers in Physiology, 2019)
PURPOSE: The main objective of this study was to investigate the physiological effects of repetitive diving-induced hyperoxic conditions at 1.35 atmospheres absolute (ATA) on neuromuscular strength performance. We hypothesized that following five days of consecutive, resting, long-duration hyperoxic water immersion (WI)s neuromuscular strength performance would be reduced with a longer recovery time in comparison to previously reported normoxic WIs. METHODS: Thirteen (n=13), active male divers [31.3 ± 1.7 (24-43) yrs, mean ± yrs] completed five consecutive 6-hour resting WIs with 18-hour surface intervals while breathing 100% O2 (n=13) at 1.35 ATA. Skeletal muscle performance assessments occurred immediately before and after each WI, and 24 and 72 hours after the final WI. Performance assessments included maximum voluntary isometric contraction (MVIC) and maximal isokinetic (IK) knee extensions and elbow flexions, and maximum handgrip strength (MHG). Neuromuscular activation was also measured on the quadriceps, biceps brachii, and brachioradialis via surface electromyography (sEMG). RESULTS: MHG declined by 7.8% (p<0.001) by WI 5 with performance returning to baseline by 24-hr post-WI. Brachioradialis neuromuscular activation increased by 42% on WI 5. MVIC knee extension performance dropped by 4% (p=0.001) on WI 3 with a 11% overall decrease in quadriceps neuromuscular activation. Maximal IK knee extension dropped by 3.3% on WI 5 with 9% drop in overall quadriceps activation during the same time period. MVIC elbow flexion declined by 5.1% on WI 5 but returned to baseline by 72-hr post-WI. Maximal IK elbow flexion performance dropped by 8.6% on WI 5 with a continual decline in biceps brachii neuromuscular activation of 24% on WI 5. CONCLUSION: Consecutive, resting, long-duration hyperoxic WIs reduce muscular performance in multiple muscle groups and alter neuromuscular activation after three days of WI with performance adaptations recovering towards baseline by the end of the WI 5. However, neuromuscular activation remains decreased and appears to last beyond the 72-hr post-WI recovery period.